TEKANAN ANGGARAN WAKTU, LOCUS OF CONTROL, SIFAT MACHIAVELLIAN, PELATIHAN AUDITOR SEBAGAI ANTESEDEN PERILAKU DISFUNGSIONAL AUDITOR - Devi, Ni Putu Arista; Ramantha, I Wayan (E-Jurnal Akuntansi, 2017)
This research is purposed to show the effect of dysfunctional behavior auditor caused by time budget pressure, locus of control, Machiavellian nature and auditor training directly with BPKP RI of the Bali Province 2016 as research location. The research sample is used saturated sample. Collecting data for the research is used survey methods with techniques for questionnaire distributed. Multiple linear regression analysis is analysis technique used in this research. Result of 54 respondents, known that time budget pressure, external locus of control, and Machiavellian nature partially significant positive associated on auditor dysfunctional behavior. Auditor training is partially significant negative effect on auditor dysfunctional behavior. Internal locus of control is partially has no effect on auditor dysfunctional behavior. Variable of time budget pressure, locus of control, Machiavellian nature, and auditor training had simultaneously influence and affect auditor dysfunctional behavior amounted 62.1 percent, while 37.9 percent is influenced by other factors.
Keywords: time budget pressure, locus of control, Machiavellian nature, auditor training, auditor dysfunctional behavior